PENGARUH INDEPENDENSI, KOMPETENSI, PENGETAHUAN DALAM MENDETEKSI KEKELIRUAN DAN PENGALAMAN AUDITOR TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS (Studi Empiris pada Kantor Akuntan Publik di Bandung) - Utami, Shinta; Anugerah, Rita; ', Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study was aimed to examine the influence of independency, competence, knowledge to detect errors , and experience of auditor to the materiality level consideration. The population of this study are auditors who worked.on the Public Accounting Firms (KAP) and listed on the Directory Indonesian Institute of Certified Public Accountants (IAPI) 2016 in Bandung. The samples of the study are all companies were selected by purposive sampling method. Based on the criteria, 50 auditor who worked on 10 KAP were chosen as the samples of this study. This study used multiple linear regression analysis was used to test whether the independent variables affect the dependent variable. Data analysis for hypothesis test was done with Statistical Package for the Social Sciences (SPSS) ver. 16. Results of regression testing (t-test) showed that the independency, competence, knowledge to detect errors, and experience of auditor have a significant relationship with the level of materiality on Public Accounting Firm (KAP) in Bandung. The amount of R Square (R2) of 0,512 gives the sense that the rate of 51,2% materiality considerations can be explained by the independency, competence, knowledge to detect errors, and experience of auditor while 48,8% can be explained by other variables.Keywords : Independency, Competence, Knowledge, Experience, and Materiality